Journal of emerging market finance. - Industrial Credit and Investment Corporation of India ([New Delhi] : Sage, 2002)
The Journal of Emerging Market Finance is a forum for debate and discussion on the theory and practice of finance in emerging markets. While the emphasis is on articles that are of practical significance, the journal also covers theoretical and conceptual aspects relating to emerging financial markets.
Mode of access: World Wide Web.
Print version record.
Volume 19, issue 2 (August 2020) (SAGE Journals, viewed August 3, 2020).
Keywords: Banks and banking -- Developing countries -- Periodicals; Financial institutions -- Developing countries -- Periodicals; Securities -- Developing countries -- Periodicals; Banks and banking; Financial institutions; Securities; Finanzmarkt; Aufstrebende Märkte.; Developing countries; finance; markten; markets; financieel beheer; financial management; geldmarkt; money market; Financial Management, Accountancy; Financieel beheer, accountancy; Electronic journals; Periodicals